2012
DOI: 10.2136/vzj2011.0120
|View full text |Cite
|
Sign up to set email alerts
|

Is the Rhizosphere Temporarily Water Repellent?

Abstract: The rhizosphere has a controlling role in the flow of water and nutrients from soil to plant roots; however, its hydraulic properties are not well understood. As roots grow, they change the pore size distribution of the surrounding soil. Roots release polymeric substances such as mucilage into their rhizosphere. Microorganisms living in the rhizosphere feed on these organic materials and release other polymeric substances into the rhizosphere. The presence of these organic materials might affect the water rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 47 publications
2
77
1
4
Order By: Relevance
“…New methods such as magnetic resonance imaging (MRI) and tomography are applied to study subterranean parts of plants (see also Skaggs and Shouse, 2008). In their contribution, Moradi et al (2012) explained the unexpected behavior of the rhizosphere observed by using neutron tomography, that is, lower soil water content in the rhizosphere compared to the bulk soil aft er rewetting. Measuring rhizosphere and soil wettability properties, they found signifi cantly higher contact angles for rhizosphere soil compared to the bulk soil aft er drying, which indicates slight water repellency in the rooting zone.…”
Section: Local Scalementioning
confidence: 99%
“…New methods such as magnetic resonance imaging (MRI) and tomography are applied to study subterranean parts of plants (see also Skaggs and Shouse, 2008). In their contribution, Moradi et al (2012) explained the unexpected behavior of the rhizosphere observed by using neutron tomography, that is, lower soil water content in the rhizosphere compared to the bulk soil aft er rewetting. Measuring rhizosphere and soil wettability properties, they found signifi cantly higher contact angles for rhizosphere soil compared to the bulk soil aft er drying, which indicates slight water repellency in the rooting zone.…”
Section: Local Scalementioning
confidence: 99%
“…They are so effective at improving soil physical conditions that biological tillage through the action of plant roots is a growing practice that is advocated in sustainable crop rotations. At the root-soil interface, the release of exudates by plant roots into the rhizosphere provides a major food source for microorganisms (Jones et al 2004), induces a physico-chemical release of nutrients for plant uptake (Malamy 2005;Marco et al 2015), and alters soil water retention and flow (Moradi et al 2012;Zarebanadkouki and Carminati 2014). Whereas a large number of studies have explored biological and chemical properties of the rhizosphere, most physical investigations are limited to measures of soil stability or pore structure visualisation, as it is difficult to perform measurements at such a small scale (Peng et al 2011;Czarnes et al 2000;Morel et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Because these compounds are common components of soil organic matter, water repellency is generally confined to the topsoils where organic matter accumulates. It is in this zone, too, that plant roots proliferate and produce root exudates that may also contribute to repellency after drying cycles as described above (Hallett et al 2003Moradi et al 2012).…”
Section: Causes (Hydrophobic Compounds) Occurrence and Measurementmentioning
confidence: 99%